The role of lncRNA SNHG15 in UV-induced DNA damage repair - Xin Zhang; Jiahui Lin; Zixuan Fan; Sai Zhang; Meiqi Yang; Tingting Zhu; Qing Lu; Yuming Wang (PLoS ONE, 2025)
Aberrant expression of long noncoding RNAs (lncRNAs) serves as a critical driver in carcinogenesis and tumor evolution across various human cancers. Among these lncRNAs, small nucleolar RNA host gene 15 (SNHG15) has emerged as a key regulator in multiple cellular processes. Its dysregulation is frequently implicated in disease pathogenesis, particularly cancer. In this investigation, we delineated the functional landscape and mechanistic basis of SNHG15 in lung carcinoma. Cell cycle synchronization experiments demonstrated phase-dependent SNHG15 expression, showing maximal transcript abundance during G2/M transition. SNHG15 knockdown substantially curbed tumor growth in vitro (A549 cell line) and in vivo (subcutaneous PDX models). Notably, SNHG15 orchestrated genomic surveillance mechanisms through tripartite regulation: (1) cell cycle checkpoint coordination, (2) transcriptional machinery reactivation, and (3) nucleotide excision repair. Mechanistically, proteomic profiling coupled with RNA immunoprecipitation identified CREB5 as a direct binding partner mediating SNHG15-dependent survival signaling under genotoxic stress. These results position the SNHG15-CREB5 axis as an important player governing genomic fidelity in lung adenocarcinoma, suggesting druggable targets for precision oncology approaches.